Mapping near-surface S-wave attenuation in the onshore southeastern flank of the Red Sea Rifting system in Saudi Arabia - Ali K. Abdelfattah; Abdulrasheed Olaniyan; Sattam Almadani; Hassan Alzahrani; Saleh Qaysi (Geomatics, Natural Hazards & Risk)
This study aims to quantify the site attenuation parameter, kappa (κ), in the southeastern flank of the Red Sea rifting system. To determine κ, a least-squares best-fit method was applied to three-component seismograms, allowing for the modelling of the Fourier amplitude spectra of S-waves. The dataset consisted of 53 earthquakes, ranging in local magnitudes from 3.0 to 4.8 ML. The estimates of κ for 17 sites in the southeastern flank of the Red Sea region revealed average values ranging from 0.026 ± 0.01s to 0.053 ± 0.01s. A statistical analysis of κ dependence on epicentral distance, near-surface geology, and earthquake magnitude demonstrated the dependence of κ on distance and surface geology rather than earthquake magnitudes. The spatial distribution of the parameter κ, which includes both path and site effects, shows higher values at soft rock sites in the eastern region than hard rock sites in the western area. Owing to surface geological conditions, the site-dependent parameter κo exhibited average values of 0.002 ± 0.003s and 0.024 ± 0.002s for the hard and soft rocks, respectively. The results may be used to improve seismic hazard assessments and earthquake ground motion simulations.